Importancia de los Hábitos Alimenticios en el Desarrollo Cognitivo de los Niños de Inicial II de la Unidad Educativa Cap. Edmundo Chiriboga de la ciudad de Riobamba, Período 2020 – 2021 - Quisilema Gallegos, Jocelyn Valeria (2021)
This investigation research aims to make know the importance of healthy eating habits in the cognitive development of children in initial education II at Unidad Educativa Cap. Edmundo Chiriboga of Riobamba city, period 2020-2021. It is important to emphasize that the information was obtained with the help of books, magazines, virtual libraries, and websites served to substantiate and achieve the objectives set out in this research, it had a mixed approach, the design of the same was non-experimental - descriptive, which has allowed to comply with the objectives established in the research, through the studies of the methods and techniques for their analysis, the observation carried out virtually on the 24 boys and girls allowed to know the context where they were developed, thanks to the collaboration of the teacher and parents, reaching the conclusion that eating habits are of relevant importance in the cognitive development of children, being this the reason for both parents and society in in general to be those who promote healthy eating to children.